The effectiveness of acceptance and commitment therapy on distress tolerance and cognitive emotion regulation in women with generalized anxiety disorder - Sarabadani , Azam; Hasanzadeh , Ramezan; Ghanadzadegan , Hosseinali (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study aims to investigate the effectiveness of treatment based on acceptance and commitment on distress tolerance and cognitive regulation of emotions in women with generalized anxiety disorder. Method: It was a semi-experimental type with a pre-test-post-test design with a control group (one experimental group and one control group) and a three-month follow-up. The statistical population of women with generalized anxiety disorder referred to counseling centers and health homes in districts 1, 2, 3 and 5 of Tehran in the first half of 2021. The sample consisted of 30 women with generalized anxiety disorder who were selected in a purposeful and accessible manner with the generalized anxiety test and having the entry criteria. to collect data from tools; "Distress Tolerance Scale", "Cognitive Emotion Regulation Questionnaire" and "Pervasive Anxiety Scale" were used. The experimental group received acceptance and commitment-based treatment intervention during two months in 8 90-minute sessions. Meanwhile, the group Evidence of this intervention was not received during the research process and a follow-up period was conducted after three months. The collected data were analyzed in SPSS.27 software. Results: The results showed that the treatment of acceptance and commitment was significantly tolerated. increased distress, adaptive strategies significantly increased cognitive regulation of emotion, and non-adaptive strategies significantly decreased cognitive regulation, and there was a significant difference in both variables between pre-test and post-test, as well as between pre-test and follow-up period. Conclusion: Treatment based on acceptance and commitment affects women with generalized anxiety disorder and improves distress tolerance and cognitive regulation of emotion in them. It is recommended to use treatment based on acceptance and commitment for women with generalized anxiety disorder.